Mortality in children and adolescents vertically infected by HIV receiving care at a referral hospital in Vitoria, Brazil - Moreira-Silva, Sandra Fagundes (BMC Infect Dis, 2015)
BACKGROUND: Daily throughout 2011, about 900 new HIV infections occurred in children and 630 children died as a result of AIDS-related complications worldwide. Late diagnosis, mortality trends, causes of and risk factors for death were evaluated in vertically HIV-infected children. METHODS: A retrospective 11-year study was conducted with Brazilian vertically HIV-infected children and adolescents using patients’ charts. Medical records, death certificates and the Ministry of Health’s mortality database were verified for mortality and cause of death. Diagnoses were made according to the CDC Revised Classification System for HIV infection. RESULTS: Of 177 patients included, 97 were female (54.8%). Median age at admission was 30 months (IQR: 5–72 months). Median follow-up was 5 years (IQR: 2–8 years). After 11 years, 132 (74,6%) patients continued in follow-up, 11 (6.2%) had been transferred and 8 (4.5%) were lost to follow-up. Twenty-six deaths occurred (14,7%), the majority (16/26; 61.5%) in children <3 years of age. Death cases decreased over time and the distribution of deaths was homogenous over the years of evaluation. In 17/26 (65.4%) of the children who died, diagnosis had been made as the result of their becoming ill. Beginning antiretroviral therapy before 6 months of age was associated with being alive (OR = 2.86; 95% CI: 1.12–7.25; p = 0.027). The principal causes of death were severe bacterial infections (57%) and opportunistic infections (33.3%). CONCLUSIONS: In most of the HIV-infected children, diagnosis was late, increasing the risk of progression to AIDS and death due to delayed treatment. The mortality trend was constant, decreasing in the final two years of the study. Bacterial infections remain as the major cause of death. Improvements in prenatal care and pediatric monitoring are mandatory.